A new species and southernmost record of Cestrus Townes (Hymenoptera, Ichneumonidae, Cryptinae) - Supeleto, Fernanda A.; Santos, Bernardo F.; Aguiar, Alexandre P. (Zootaxa, 2020)
Cestrus itatiensis sp. nov., from the Brazilian Atlantic Forest, is described and illustrated. This is the southernmost record for the genus and the first record in Brazil. The new species is characterized by having the body reddish brown; a narrow yellow stripe along eye margin on supra-clypeal area, reaching briefly the supra-antennal area; transverse carina of propodeum complete and stout; postpetiole and T2–8 progressively dark brown towards apical margin in a somewhat triangular pattern; and apex of dorsal valve of ovipositor with nine distinct teeth. Extensive sampling suggest this is a rare species.